Lithium and Chlorine-Rich Preparation of Mechanochemically Activated Antiperovskite Composites for Solid-State Batteries - Yang, Yi; Han, Joah; DeVita, Michael; Lee, Stephanie S.; Kim, Jae Chul (Frontiers in Chemistry, 2020)
Assembling all-solid-state batteries presents a unique challenge due to chemical and electrochemical complexities of interfaces between a solid electrolyte and electrodes. While the interface stability is dictated by thermodynamics, making use of passivation materials often delays interfacial degradation and extends the cycle life of all-solid cells. In this work, we investigated antiperovskite lithium oxychloride, Li3OCl, as a promising passivation material that can engineer the properties of solid electrolyte-Li metal interfaces. Our experiment to obtain stoichiometric Li3OCl focuses on how the starting ratios of lithium and chlorine and mechanochemical activation affect the phase stability. For substantial LiCl excess conditions, the antiperovskite phase was found to form by simple melt-quenching and subsequent high-energy ball-milling. Li3OCl prepared with 100% excess LiCl exhibits ionic conductivity of 3.2×10-5 S cm-1 at room temperature, as well as cathodic stability against Li metal upon the extended number of cycling. With a conductivity comparable to other passivation layers, and stable interface properties, our Li3OCl/LiCl composite has the potential to stably passivate the solid-solid interfaces in all-solid-state batteries.